(untitled) (Tempo e Argumento, 2011)
This paper aims to historiographically interpret conflicts permeating the heritage-listing process of an old railway station in the city of Joinville, Santa Catarina. The research has been based on historians writings, newspapers and municipality official documents as well as oral history sources. Different meanings of the terms of history, memory and cultural heritage present in speeches about the Railway Station of Joinville are discussed. I seek to demonstrate that the multiple approaches to this cultural heritage refer to social experiences with the present, the past and the future. Finally, in contemporary times, I think that the public protection and management policies of urban cultural heritage must focus more on social appropriation processes than on the referenced buildings.